A Comparative Economic Feasibility Study of Photovoltaic Heat Pump Systems for Industrial Space Heating and Cooling - Celena Lorenzo; Luis Narvarte; Ana Belén Cristóbal (Energies, 2020)
The use of photovoltaic (PV) systems for powering heat pumps (HP) leads to an economic, energy efficient and environmentally friendly alternative for heating and cooling generation. A technical solution developed by the authors permits stand-alone configurations to operate without batteries, mitigating up to 75% of the solar power fluctuations resulting from cloud-passing. Once its technical feasibility has been demonstrated, the economic potential of this innovative solution should be assessed (avoiding a battery system is a significant advantage). This paper presents a comparative economic assessment of this autonomous (AU) solution and a self-consumption (SC) solution, that would substitute a grid-powered HP system for the space heating and cooling of two livestock farms located in Spain. Results show that PV-HP systems are economically feasible regardless of the technical solution: the Profitability Index (PI) is in the 2.23–2.97 €/€ range, the Internal Rate of Return (IRR) is in the 8.1–10.9% range, the Payback Period (PBP) is in the 9.2–11 years range and the savings in terms of the Levelized Cost of Energy (LCOE) are in the 57–70% range. The AU solution offers a higher economic profitability, because it permits larger savings in the electricity bill. The SC solution presents lower LCOEs because of its greater electricity production.